Analisa Fiskal di Provinsi Jawa Barat Periode 2019-2021 - Abdul Mutholib; Selly Apriliani; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
ABSTRACT The requirement to implement regional autonomy and fiscal decentralization is a good regional fiscal health condition. This study took a sample of districts / cities in West Java Province in the period 2019 - 2021 to be analyzed using the Fiscal Health Index. The research method uses a quantitative descriptive study and as the unit of analysis sets all districts / cities. The fiscal health condition of each Regency / City in the West Java Province region before and during the Covid-19 pandemic can be described through the results of the analysis. From the measurement of each indicator, it can be seen that the regions with good financial health conditions are Pangandaran Regency, Majalengka Regency, Cirebon City, and Banjar City. The financial condition of Pangandaran Regency is relatively stable, even though the two years of the Covid-19 pandemic have not experienced significant shocks. Likewise with Majalengka Regency, although the index fell at the beginning of the pandemic (2019, and 2020), in 2021 the index increased significantly. On the other hand, the financial health conditions that are classified as poor are Cianjur, Karawang, and West Bandung. These three regions have a financial condition index far from other regions. In 2019, West Bandung Regency and in 2021 Cianjur Regency are the regions with the lowest index while in 2020 the lowest is Karawang Regency. Keywords: Regional Fiscal Health, Fiscal Decentralization, Financial Independence, Financial Flexibility, Service Solvency